2012
DOI: 10.1111/j.1528-1167.2012.03544.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural white matter abnormality and frontal cognitive dysfunctions in juvenile myoclonic epilepsy

Abstract: SUMMARYPurpose: Previous neuroimaging studies provide growing evidence that patients with juvenile myoclonic epilepsy (JME) have both structural and functional abnormalities of the thalamus and frontal lobe gray matter. However, limited data are available regarding the issue of white matter (WM) involvement, making the microstructural WM changes in JME largely unknown. In the present study we investigated changes of WM integrity in patients with JME, and their relationships with cognitive functions and epileps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
79
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 50 publications
14
79
3
2
Order By: Relevance
“…Lee et al [28] suggested that DKI-based tractography may allow for a more complete characterization of asymmetrical neural networks with a clinically feasible scan time (7 min), suggesting that DKI-based tractography may be useful to study disease processes that are associated with structural asymmetries. Previous DTI studies in IGE reported regional microstructural abnormalities, such as in the anterior limb of the internal capsule, anterior and superior corona radiation, corpus callosum and superior and inferior longitudinal fasciculus [2,3,29,30]. These abnormalities reported by separate studies are mostly encompassed by our observed DKI metrics.…”
Section: Discussionsupporting
confidence: 65%
“…Lee et al [28] suggested that DKI-based tractography may allow for a more complete characterization of asymmetrical neural networks with a clinically feasible scan time (7 min), suggesting that DKI-based tractography may be useful to study disease processes that are associated with structural asymmetries. Previous DTI studies in IGE reported regional microstructural abnormalities, such as in the anterior limb of the internal capsule, anterior and superior corona radiation, corpus callosum and superior and inferior longitudinal fasciculus [2,3,29,30]. These abnormalities reported by separate studies are mostly encompassed by our observed DKI metrics.…”
Section: Discussionsupporting
confidence: 65%
“…Riley et al (2010) have found earlier age at seizure onset correlated with reduced FA in the corpus callosum in adults with temporal lobe epilepsy. Kim et al (2012b) found FA reduction in superior and anterior corona radiata, corpus callosum and middle and superior frontal WM tracts correlated with the number of generalized tonic clonic seizures in patients with juvenile myoclonic epilepsy. There is as yet no explanation for the lack of consensus in findings; differences in underlying cause and types of seizures may potentially contribute to some of the differences observed.…”
Section: Discussionmentioning
confidence: 78%
“…DTI studies have been reported in patients with epilepsy associated with frontal lobe dysfunction and they have found similar findings. DTI studies in juvenile myoclonic epilepsy, an idiopathic generalized epilepsy with frontal lobe dysfunctions, showed abnormal WM in supplementary motor area, bilateral superior and anterior corona radiata, genu and body of corpus callosum, and multiple superior and middle frontal WM tracts, and thalamofrontal connections (Deppe et al, 2008;Kim et al, 2012b;O'Muircheartaigh et al, 2011). The WM in the frontal lobe has also been examined using DTI in 12 children with drug resistant partial epilepsy (Holt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with JME show lower FA in fornix, corpus callosum, uncinate fasciculi, superior longitudinal fasciculi, internal capsule, and corticospinal tracts compared with patients with IGE-GTCS. Focal diffusion abnormalities in the supplementary motor area (SMA), posterior cingulate cortex, and corpus callosum [191][192][193][194] suggest reduced structural connectivity of mesial frontal cortex, explaining the frontal lobe dysfunction 192,193,195 in JME. However, structural and functional connectivity between the prefrontal and motor cortex is increased, 196 and increased coactivation of the motor cortex and SMA with increased cognitive load may represent the anatomic basis for cognitive triggering of myoclonic jerks.…”
Section: Hs Resultsmentioning
confidence: 99%